EFISIENSI PRODUKSI AYAM BROILER DI KECAMATAN RUMBAI KOTA PEKANBARU PROVINSI RIAU - Elinur Elinur; Sisca Vaulina (DINAMIKA PERTANIAN, 2019)
ABSTRACT The research aims to analyze the level of production efficiency from technical, allocative and economic aspects. The research used a survey method which is located in Rumbai district, Pekanbaru City. The research used cross-section data which were obtained by personal interviews. Samples were selected using a simple random sampling method with a total of 40 broiler chicken breeders. Data Analysis used the Data Envelopment Analysis (DEA) technique. The result showed that broiler chicken breeders were technically efficient as much as 40 percent, and 12.5 percent were allocative and economically efficient. In general, broiler chicken breeders were not technically, allocative and economically efficient. The inefficiency of broiler chicken breeders is caused by the in-optimal of using production factors of broiler chicken breeders.